Association of Caveolin-1 Expression With Prostate Cancer: A Systematic Review and Meta-Analysis - Chen, Pei; Zhang, Yu-ling; Xue, Bai; Xu, Guo-ying (Frontiers in Oncology, 2021)
Purpose The prognostic value of caveolin-1 in prostate cancer remains uncertain. Hence, this meta-analysis was performed to evaluate the prognostic value of caveolin-1 in prostate cancer, as well as ascertain the relationship between caveolin-1 expression and clinicopathological characteristics of prostate cancer patients. Methods The PubMed, Embase, Chinese National Knowledge Infrastructure and Chinese Biology Medicine databases were electronically searched to retrieve published studies on caveolin-1 expression in prostate cancer. After study selection and data extraction, the meta-analysis was conducted using Review manager 5.3 software. Odds ratio (OR) with 95% confidence interval (CI) was used to estimate the pooled effect. Funnel plot was used to assess publication bias. Results A total of ten studies were enrolled, which included 3976 cases of prostate cancer, 72 cases of high-grade intraepithelial neoplasia (HGPIN), and 157 normal controls. Results of the meta-analysis showed that the positive rate of caveolin-1 expression in prostate cancer was 18.28 times higher than that in normal control (OR= 18.28, 95% CI: 9.02–37.04, p<0.01), and 4.73 times higher than that in HGPIN (OR= 4.73, 95% CI: 2.38–9.42, p<0.01). The relationship between caveolin-1 and clinicopathological characteristics of prostate cancer showed that the differences in caveolin-1 expression in patients with prostate-specific antigen (PSA) >10 vs. ≤ 10 (OR=2.09, 95% CI: 1.35–3.22, p<0.01), differentiation degree low vs. medium/high (OR=2.74, 95% CI: 1.84–4.08, p<0.01), TNM stage T3+T4 vs. T1+T2 (OR=2.77, 95% CI: 1.78–4.29, p<0.01), and lymph node metastasis present vs. absent (OR=2.61, 95% CI: 1.84–3.69, p<0.01) were statistically significant. The correlation analysis between caveolin-1 and the survival time of patients with prostate cancer demonstrated that caveolin-1 was closely related to the prognosis of prostate cancer patients (HR=1.50, 95% CI: 1.28–1.76, p<0.01). Conclusion Caveolin-1 is overexpressed in prostate cancer, which can serve as a risk factor and adverse clinicopathological feature of prostate cancer. Caveolin-1 can also predict poor survival in prostate cancer patients after radical prostatectomy.